Weak Scale Effects in Growth Models - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
Growth models of the second generation type, e.g. the Jones (1995) or Young (1998) model, all exhibit a so called weak scale effect in per capita production, i.e. larger economies should have a higher per capita production than smaller economies. However, in an open economy context the scale of the economy is less important because countries can participate in the scale of other countries through trade. This paper develops a simple open economy growth model of the second generation type which shows the relevance of the scale of the trading partners for per capita production. This model is empirically tested using time series for the G7 countries and alternatively a cross section of 80 countries for the year 2000. The scale of these economies is measured by their own scale as well as the scale of their major trading partners. The results show that there is a significant effect of the own scale and the scale of the trading partners on per capita production. Additionally the paper provides a theoretical model that shows the relevance of the weak scale effect in explaining wage inequality between different types of workers.
urn:nbn:de:bvb:384-opus4-347294
Keywords: F12; F43; O47; 330; Growth and Scale Effects; International Trade